A CHECKLIST TO ASSESS THE USE OF DISCOURSE MARKERS IN STUDENTS’ WRITING - Erma Sujiyani; Atiqah Nurul Asri; Maya Rizki Fauzia; Nur Mukminatien (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2014)
Discourse markers (DMs) play a crucial role in writing as ‘linking words’, ‘linking phrases’, or ‘sentence connectors’ that bind ideas between sentences in a paragraph  or between paragraphs to  build  coherence  in a text.  DMs should be sufficiently but not overly used in writing. As EFL learners find it difficult to identify the types, functions, and positions of DMs to link ideas in their academic writing, this article attempts to share an instrument in the form of DMs checklist to help learners enhance their knowledge of DMs. The checklist can also be used as teacher/peer feedback form in the writing process.